Scientific American Supplement, No. 447, July 26, 1884 - Various (Salt Lake City, UT : Project Gutenberg, 2005)
"Scientific American Supplement, No. 447, July 26, 1884" by Various is a scientific publication from the late 19th century. The issue includes a variety of articles covering advancements in chemistry, engineering, technology, natural history, geology, and more, providing readers insight into contemporary scientific discussions and innovations of that time. The opening of this issue presents a table of contents and introduces topics such as improvements in the harbor of Antwerp, featuring detailed descriptions of engineering techniques employed to enhance the port's capacity and efficiency. It discusses the meteorological advancements impacting shipping routes, while articles on bicycles and tricycles indicate a growing interest in personal transportation innovations. It also introduces a focus on various scientific investigations, such as the chemistry behind hop bitterness and the analysis of coal, showcasing the intersection of industrial progress and scientific research during this transformative era. (This is an automatically generated summary.)
Release date is 2005-11-01
Produced by Don Kretz, Juliet Sutherland, and Distributed Proofreaders
Keywords: Science -- Periodicals